2015
DOI: 10.1038/ncomms9494
|View full text |Cite|
|
Sign up to set email alerts
|

EZH2-mediated loss of miR-622 determines CXCR4 activation in hepatocellular carcinoma

Abstract: The CXC chemokine receptor 4 (CXCR4) exerts a variety of functions at different steps of hepatocellular carcinoma (HCC) progression. The molecular mechanisms and therapeutic value of CXCR4 in the development of HCC remain undefined. Here we show that aberrant CXCR4 overexpression is associated with poor prognosis and aggressive characteristics of HCC. Suppression of CXCR4 activity via CXCR4 knockdown, AMD3100 or neutralizing antibody administration inhibits hepatoma cell tumorigenesis in vitro and in vivo. CXC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
86
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 42 publications
11
86
0
1
Order By: Relevance
“…We focused on the effects of miRNAs on YTHDF2. Bioinformatics analysis predicted the potential miRNAs targeting the 3Ј-UTR of YTHDF2 by using three websites, including DIANA-microT, Targetscan, and MiRanda (33). Interestingly, eight candidate miRNAs could be predicted (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We focused on the effects of miRNAs on YTHDF2. Bioinformatics analysis predicted the potential miRNAs targeting the 3Ј-UTR of YTHDF2 by using three websites, including DIANA-microT, Targetscan, and MiRanda (33). Interestingly, eight candidate miRNAs could be predicted (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These data are in line with two recent reports that also described a tumour-suppressive function of miR-622 in HCC. Liu et al identified miR-622 as negative regulator of CXC chemokine receptor 4 (CXCR4) in HCC and showed that the inhibitory effect of miR-622 on migration of HCC cells strongly depends on CXCR4 suppression 32. In contrast, growth-suppressive effects of miR-622 on HCC cells were only slightly affected by its effect on CXCR4 expression 32.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al identified miR-622 as negative regulator of CXC chemokine receptor 4 (CXCR4) in HCC and showed that the inhibitory effect of miR-622 on migration of HCC cells strongly depends on CXCR4 suppression 32. In contrast, growth-suppressive effects of miR-622 on HCC cells were only slightly affected by its effect on CXCR4 expression 32. Song et al found that miR-622 negatively regulates mitogen-activated protein 4 kinase 4 (MAP4K4) in HCC, but overexpression of MAP4K4 only partially reversed the growth-suppressive effects of miR-622 on HCC cells 31.…”
Section: Discussionmentioning
confidence: 99%
“…For example, abnormal methylation of the HOXB4 gene leads to the inactivation of miR-10a, resulting in the activation of the NFjB signaling pathway in human HCC tumor tissues [96]. In addition, methylation-mediated repression of several microRNAs correlates with tumor aggressiveness of human HCC [97][98][99].…”
Section: Epigenetics Of Hepatitis Virus-related Hccmentioning
confidence: 99%